Local food hubs in deprived areas: de-stigmatising food poverty?. Issue 6 (3rd June 2019) - Psarikidou, Katerina; Kaloudis, H.; Fielden, A.; Reynolds, C.
ABSTRACT: This paper aims to explore the potential of "local food hubs" to address issues of stigma associated with the use of food banks in urban deprived areas. "Local Food Hubs" are a relocalised distribution channel, however, like other Alternative Agro-Food Networks (AAFNs), it can be an elite phenomenon for affluent areas and consumers. Our research focuses on the Open Food Network (OFN) local food hubs in order to explore their potential to constitute "an alternative" to the conventional ways of addressing food poverty. Currently, food banks are the main avenue for accessing food in conditions of food poverty, carrying significant implications of stigmatisation for their users. In this paper, drawing on existing social science research on stigma, we identify the diverse ways "local food hubs" help overcome as well as reproduce existing discourses and practices of stigmatisation. We conclude that, despite their efforts, as they currently stand, "local food hubs" are unable to address stigma in food poverty. We suggest that his is due to the specific individual-focused stigma-management strategies they employ, as well as the wider underlying societal structures that cause food poverty, and which local food hubs are unable to address by themselves. We thus propose that addressing the broader structural conditions that cause and reproduce stigma in food poverty is pivotal for "local food hubs" to be in a position to constitute an AAFN for all.